Stranded: o desenvolvimento de uma história em quadrinhos e sua divulgação - Franci, Lucas de Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Stranded is a project that consists of the creation of a webcomic that will be published in 2017. The project involves character, background and creature design, the development of a story and ultimately the creation of a digitally animated 2D short film. The animation was thought in a teaser-trailer format, with the demonstration of a small sequence of scenes that represents part of a whole well enough to instigate the spectators, and make them want to experience the final product, which is the webcomic. With approximatedly two and a half minuets of length, the short film transports the beginning of the protagonist's journey into a animated world to create an impact and show all the visual and narrative of Stranded's story. Key-words: animation, science ficction, webcomic

Stranded é o projeto de criação de uma webcomic a ser publicada em 2017. O projeto envolve design de personagens, cenários e criaturas, desenvolvimento de uma história e por último a criação de um curta metragem 2D animado digitalmente. A animação foi pensada no formato de teaser-trailer, com a demonstração de uma pequena sequência de cenas que representa parte de um todo suficientemente bem para instigar os espectadores, e deixá-los com vontade de consumir o produto final, a webcomic. Com aproximadamente dois minutos e meio, o curta transporta o início da jornada do protagonista para um mundo animado para causar impacto e mostrar o potencial visual e narrativo da história de Stranded
Keywords: Imagens digitais; Histórias em quadrinhos; Animação (Cinematografia); Digital images